Utilisation of Animal Husbandry Extension Services by Rainfed Farmers - G.R.Desai; P.L.Manohari (Journal of Agricultural Extension Management, 2025)
The State Departments of Animal Husbandry in India are the major agencies responsible for delivery of extension services to the farming community. The department has other important activities like promotion of cattle, buffalo, piggery, poultry, sheep, goat production along with development of fodder, training, implementation of socioeconomic programmes etc